Silica Sulfuric Acid-Catalyzed One-Pot Synthesis of 1,3-Diarylimidazolium Tetrafluoroborate - Wan, Yu; Zhang, Wen-Li; Cui, Hao; Zhang, Li-Zhuo; Zhou, Qiu-Ju; Zou, Huan; Wang, Yuan-Jiang; Ge, Wen-Hui; Fang, Yue; Zhou, Sheng-Liang; Wu, Hui (Asian Journal of Chemistry, 2015)
A silica sulfuric acid-catalyzed three-component one-pot synthesis of 1,3-diarylimidazolium tetrafluoroborates was undertaken via the reaction of aromatic amine, formaldehyde and glyoxal at room temperature in ionic liquid [BMIM][BF4] with good yields. Up to four new bonds and one new ring were formed in one-pot with water as the only by-product in the reactions. The product 4d was determined by X-ray diffraction. This work develops an efficient and low-cost preparation of 1,3-diarylimidazolium and N-heterocylic carbene.